Early Diagnosis of Pancreatic Ductal Adenocarcinoma by Combining Relative Expression Orderings With Machine-Learning Method - Zhang, Zi-Mei; Wang, Jia-Shu; Zulfiqar, Hasan; Lv, Hao; Dao, Fu-Ying; Lin, Hao (Frontiers in Cell and Developmental Biology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive and lethal cancer deeply affecting human health. Diagnosing early-stage PDAC is the key point to PDAC patients’ survival. However, the biomarkers for diagnosing early PDAC are inexact in most cases. Therefore, it is highly desirable to identify an effective PDAC diagnostic biomarker. In current work, we designed a novel computational approach based on within-sample relative expression orderings (REOs). A feature selection technique called minimum redundancy maximum relevance (mRMR) was used to pick out optimal REOs. We then compared the performances of different classification algorithms for discriminating PDAC and its adjacent normal tissues from non‐PDAC tissues. The support vector machine (SVM) algorithm is the best one for identifying early PDAC diagnostic biomarker. At first, a signature composing of 9 gene pairs was acquired from microarray gene expression data sets. These gene pairs could produce a satisfactory classification accuracy up to 97.53% in five-fold cross-validation. Subsequently, two types of data from diverse platforms namely: microarray and RNA-Seq, were used to validate this signature. For microarray data, all (100.00%) of 115 PDAC tissues and all (100.00%) of 31 PDAC adjacent normal tissues were correctly recognized as PDAC. And 88.24% of 17 non-PDAC (normal or pancreatitis) tissues were correctly classified. For the RNA-Seq data, all (100.00%) of 177 PDAC tissues and all (100.00%) of 4 PDAC adjacent normal tissues were correctly recognized as PDAC. Validation results demonstrated that the signature had a good cross platform effect for early detection of PDAC. This work developed a new robust signature that might be a promising biomarker for early PDAC diagnosis.